2016
DOI: 10.1016/j.hal.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous distribution in sediments and dispersal in waters of Alexandrium minutum in a semi-enclosed coastal ecosystem

Abstract: Within the framework of research aimed at using genetic methods to evaluate harmful species distribution and their impact on coastal ecosystems, a portion of the ITS1rDNA of Alexandrium minutum was amplified by real-time PCR from DNA extracts of superficial (1-3cm) sediments of 30 subtidal and intertidal stations of the Bay of Brest (Brittany, France), during the winters of 2013 and 2015. Cell germinations and rDNA amplifications of A. minutum were obtained for sediments of all sampled stations, demonstrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…where the maximum occurrences of toxic algal blooms are observed today within the Bay of Brest (Klouch et al, 2016a), also corresponds to the site where maximal percentages of agriculture-type pollen markers are observed in Bay of Brest modern sediments (Lambert et al, 2017), confirming the link between increased runoff on agricultural soils and the disturbance of the phytoplankton community. This may be related to the small size of the watershed and the isolation of the Daoulas estuary from main tidal currents.…”
Section: Accepted Manuscriptmentioning
confidence: 52%
See 1 more Smart Citation
“…where the maximum occurrences of toxic algal blooms are observed today within the Bay of Brest (Klouch et al, 2016a), also corresponds to the site where maximal percentages of agriculture-type pollen markers are observed in Bay of Brest modern sediments (Lambert et al, 2017), confirming the link between increased runoff on agricultural soils and the disturbance of the phytoplankton community. This may be related to the small size of the watershed and the isolation of the Daoulas estuary from main tidal currents.…”
Section: Accepted Manuscriptmentioning
confidence: 52%
“…In this study, a core from the outlet of the Daoulas Estuary in the Bay of Brest has provided a very high-resolution palynological record from 1870 AD to present. The Daoulas Bay records today the most intense toxic bloom of dinoflagellates Alexandrium minutum within the Bay of Brest (Klouch et al 2016a). Furthermore, the palaeobiodiversity of dinoflagellate communities has been recently reported on the same sampled Daoulas core with molecular data (Klouch et al, 2016b), suggesting a great increase in bloom frequency of this toxic species A. minutum over the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…The MARS 3D model of the Bay of Brest (limits: 48.20°N -48.44°N and 4.09°W -4.72°W) has a horizontal resolution of 50 m, with 20 sigma layers for vertical coordinates (equidistant layers throughout the domain that change with sea surface elevation). The model has already been validated on temperature and salinity datasets (Petton S. et al, unpublished) and previously used for trajectories of toxic algal cells released from estuarine zones (Klouch et al, 2016 mesh of the whole hydrodynamic model inside the bay, which led to a total of 1,437,500 passive particles for each run. Coastline behaviour was set as beaching, as the MARS 3D model is implemented with a wetting-drying numerical method in intertidal areas.…”
Section: Surface Dispersal Modellingmentioning
confidence: 99%
“…Indeed, it would be of great interest to further refine details on outputs and sources. Klouch et al (2016) studied the trajectories of Alexandrium minutum cells in the surface water of the Bay of Brest, considering only the mouth of the main rivers where the blooms of A. minutum occur. Considering estuaries as starting points for A. minutum cell release, the retention of the particles appeared higher, from 56 to 81%, compared to our study.…”
Section: Spatial and Temporal Variability In The Distribution Of Floamentioning
confidence: 99%
“…Most of the sedimentation takes place in the inner zone of estuaries because tidal energy is stronger than river flow (Dyer, 1997;Moskalski et al, 2018). Klouch et al (2016a) demonstrated that the south-east of the bay is disconnected from the Elorn estuary, which is the area exporting the highest proportion of particles outside the BB.…”
Section: Hydrological Hydrodynamic and Modern Sedimentary Settingsmentioning
confidence: 99%